Maternal outcomes at 3 months after planned caesarean section versus planned vaginal birth for twin pregnancies in the Twin Birth Study: a randomised controlled trial - Hutton, E.K.; Hannah, M.E.; Joseph, K.S.; Ohlsson, A.; Asztalos, Elizabeth; Willan, A.C.; Armson, B.A.; Gafni, A.; Mangoff, K.; Sanchez, J.J.; Barrett, J.F.; Thornton, Jim (Wiley, 2015)
OBJECTIVE: To compare outcomes at 3 months post partum for women randomised to give birth by planned caesarean section (CS) or by planned vaginal birth (VB) in the Twin Birth Study (TBS). DESIGN: We invited women in the TBS to complete a 3-month follow-up questionnaire. SETTING: Two thousand and eight hundred and four women from 25 countries. POPULATION: Two thousand and five hundred and seventy women (92% response rate). METHODS: Women randomised between 13 December 2003 and 4 April 2011 in the TBS completed a questionnaire and outcomes were compared using an intention-to-treat approach. MAIN OUTCOME AND MEASURES: Breastfeeding, quality of life, depression, fatigue and urinary incontinence. RESULTS: We found no clinically important differences between groups in any outcome. In the planned CS versus planned VB groups, breastfeeding at any time after birth was reported by 84.4% versus 86.4% (P = 0.13); the mean physical and mental Short Form (36) Health Survey (SF-36) quality of life scores were 51.8 versus 51.6 (P = 0.65) and 46.7 versus 46.0 (P = 0.09), respectively; the mean Multidimensional Assessment of Fatigue score was 20.3 versus 20.8 (P = 0.14); the frequency of probable depression on the Edinburgh Postnatal Depression Scale was 14.0% versus 14.8% (P = 0.57); the rate of problematic urinary incontinence was 5.5% versus 6.4% (P = 0.31); and the mean Incontinence Impact Questionnaire-7 score was 20.5 versus 20.4 (P = 0.99). Partner relationships, including painful intercourse, were similar between the groups. CONCLUSION: For women with twin pregnancies randomised to planned CS compared with planned VB, outcomes at 3 months post partum did not differ. The mode of birth was not associated with problematic urinary incontinence or urinary incontinence that affected the quality of life. Contrary to previous studies, breastfeeding at 3 months was not increased with planned VB. TWEETABLE ABSTRACT: Planned mode of birth for twins doesn't affect maternal depression, wellbeing, incontinence or breastfeeding.